PENINGKATAN LITERASI KEUANGAN SYARIAH MELALUI PELATIHAN PENGELOLAAN DAN KEUANGAN MASJID DI KARANGPILANG SURABAYA - Nurwinsyah Rohmaningtyas; Ach Yasin; Ramdani Ramdani; Moch Khoirul Anwar; Chiquita Kumala Putri Subagjo (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
Currently, the Indonesian Mosque Council has management at the provincial and city district levels. One of the managements at the Regency/City Level is the Indonesian Mosque Council (DMI) of Surabaya City. DMI Surabaya City has 26 branches and oversees 1,759 mosques, according to data from the Central Statistics Agency (BPS) regarding the number of mosques in Surabaya in 2023. However, the obstacle for mosque administrators currently is that they still do not know how to manage mosque funds well. Hopely, the mosque takmir can make plans for the mosque's financial potential which can be managed effectively and efficiently with the aim of providing benefits to the people. The purpose of this service is to introduce the community, especially the mosque takmir in Surabaya about sharia finance and how to manage and administer the mosque accordance with sharia. The method used is Community-Based Research (CBR), starting from problem identification, discussions with partners then offering solutions, socializing them followed by evaluation and ends with the report.